The effect of probability discounting on reward seeking: a three-dimensional perspective - Breton, Yannick-Andre; Conover, Kent; Shizgal, Peter (Frontiers in Behavioral Neuroscience, 2014)
Rats will work for electrical stimulation of the medial forebrain bundle. The rewarding effect arises from the volleys of action potentials fired by the stimulation and subsequent spatio-temporal integration of their post-synpatic impact. The proportion of time allocated to self-stimulation depends on the intensity of the rewarding effect as well as on other key determinants of decision-making, such as subjective opportunity costs and reward probability. We have proposed that a 3D model relating time allocation to the intensity and cost of reward can distinguish manipulations acting prior to the output of the spatio-temporal integrator from those acting at or beyond it. Here, we test this proposition by varying reward probability, a variable that influences the computation of payoff in the 3D model downstream from the output of the integrator. On riskless trials, reward was delivered on every occasion that the rat held down the lever for a cumulative duration called the “price,” whereas on risky trials, reward was delivered with probability 0.75 or 0.50. According to the model, the 3D structure relating time allocation to reward intensity and price is shifted leftward along the price axis by reductions in reward probability; the magnitude of the shift estimates the change in subjective probability. The predictions were borne out: reducing reward probability shifted the 3D structure systematically along the price axis while producing only small, inconsistent displacements along the pulse-frequency axis. The results confirm that the model can accurately distinguish manipulations acting at or beyond the spatio-temporal integrator and strengthen the conclusions of previous studies showing similar shifts following dopaminergic manipulations. Subjective and objective reward probabilities appeared indistinguishable over the range of 0.5 ≤ p ≤ 1.0.